2016
DOI: 10.15171/jrip.2017.35
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effects of grape seed extract in hemodialysis patients; a pilot study

Abstract: Immune responses and inflammation are major risk factors for mortality in patients with end-stage renal disease (ESRD). Increased oxidative stress is a common feature of ESRD, and it has been speculated that it is interrelated to inflammation. In many studies it has been proved that red grape seed extract (RGSE) provides an antioxidant efficacy. Objectives: The aim of this study was to investigate the anti-inflammatory effects of RGSE in hemodialysis patients. Patients and Methods: Thirty hemodialysis individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(33 citation statements)
references
References 13 publications
(14 reference statements)
0
33
0
Order By: Relevance
“…After screening 724 studies, 15 (Abedini et al, ; Alirezaei et al, ; Argani et al, ; Clifton, ; Kar, Laight, Rooprai, Shaw, & Cummings, ; Mellen, Daniel, Brosnihan, Hansen, & Herrington, ; Park, Edirisinghe, Choy, Waterhouse, & Burton‐Freeman, ; Pourghassem‐Gargari, Abedini, Babaei, Aliasgarzadeh, & Pourabdollahi, ; Sano et al, ; Sivaprakasapillai, Edirisinghe, Randolph, Steinberg, & Kappagoda, ; Taghizadeh, Malekian, Memarzadeh, Mohammadi, & Asemi, ; Terauchi et al, ; Turki et al, ; Vigna et al, ; Ward et al, ) of them were eligible to be included in this meta‐analysis. These studies were detected by a process that is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After screening 724 studies, 15 (Abedini et al, ; Alirezaei et al, ; Argani et al, ; Clifton, ; Kar, Laight, Rooprai, Shaw, & Cummings, ; Mellen, Daniel, Brosnihan, Hansen, & Herrington, ; Park, Edirisinghe, Choy, Waterhouse, & Burton‐Freeman, ; Pourghassem‐Gargari, Abedini, Babaei, Aliasgarzadeh, & Pourabdollahi, ; Sano et al, ; Sivaprakasapillai, Edirisinghe, Randolph, Steinberg, & Kappagoda, ; Taghizadeh, Malekian, Memarzadeh, Mohammadi, & Asemi, ; Terauchi et al, ; Turki et al, ; Vigna et al, ; Ward et al, ) of them were eligible to be included in this meta‐analysis. These studies were detected by a process that is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…General characteristics of eligible studies are summarized in Table . The studies were conducted in Italy (Vigna et al, ), Australia (Clifton, ; Ward et al, ), Japan (Sano et al, ; Terauchi et al, ), United Kingdom (Kar et al, ), United States (Mellen et al, ; Park et al, ; Sivaprakasapillai et al, ), Iran (Abedini et al, ; Alirezaei et al, ; Argani et al, ; Pourghassem‐Gargari et al, ; Taghizadeh et al, ), and Tunisia (Turki et al, ). Studies were published between 2003 and 2017.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations